2019
DOI: 10.1111/hsc.12731
|View full text |Cite
|
Sign up to set email alerts
|

Professional care at home: Patient‐centredness, interprofessionality and effectivity? A scoping review

Abstract: The aim of this scoping review was to describe the state of knowledge on professional care at home with regard to different perspectives on patient-centredness, content of care, interprofessional collaboration, competence framework and effectivity. A scoping review, n = 35 papers, from four databases (EBSCO, CINAHL, Medline, Swemed) were reviewed between May and August 2018 using the terms:hospital-at-home, hospital-in-the-home, advanced home healthcare, hospital-based home care or patient-centered medical hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 41 publications
1
51
0
1
Order By: Relevance
“…HAH can be offered as form of primary, specialized or private care or as a combination of these. In one scoping review (Vaartio‐Rajalin & Fagerström, , N = 35), researchers found that before a planned hospital stay or in conjunction with hospital discharge, a physician or a rapid response team should conduct a holistic assessment of a patient's physical and psychological health, acute and chronic symptoms, symptom distress, functional status, disease stage, comorbidities and motivation. This assessment could be performed at the hospital, during a proactive or acute, unscheduled home visit or by telephone call.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…HAH can be offered as form of primary, specialized or private care or as a combination of these. In one scoping review (Vaartio‐Rajalin & Fagerström, , N = 35), researchers found that before a planned hospital stay or in conjunction with hospital discharge, a physician or a rapid response team should conduct a holistic assessment of a patient's physical and psychological health, acute and chronic symptoms, symptom distress, functional status, disease stage, comorbidities and motivation. This assessment could be performed at the hospital, during a proactive or acute, unscheduled home visit or by telephone call.…”
Section: Introductionmentioning
confidence: 99%
“…HAH is realized in interprofessional teams (comprised of a physician/geriatrician and a nurse; possibly even social workers, pharmacists, nutrition therapists or physiotherapists) together with patient's near‐ones. In regard to the nursing being provided, HAH activities are realized by either registered nurses (RNs), district nurses (DNs) or advanced practitioner nurses (APNs) (Vaartio‐Rajalin & Fagerström, . ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations